Electrochemical detection of cholesterol based on competitive host–guest recognition using a β-cyclodextrin/poly(N-acetylaniline)/graphene-modified electrode. Issue 79 (28th August 2015) - Yang, Long; Zhao, Hui; Fan, Shuangmei; Zhao, Genfu; Ran, Xin; Li, Can-Peng
<x xml:space="preserve">Abstract</x> Illustration of the strategy of the proposed electrochemical sensor based on the competitive host–guest interaction between β-CD and MB (signal probe)/cholesterol (target).